“Arte-facts” - Stylianou-Lambert, Theopisti (My University, 2020)
“Arte-facts” is a photography project that looks into the relationships of Cypriots with archaeology. The emphasis is on alternative narratives and omissions: the unacknowledged and unnamed Cypriot worker at archaeological excavations, the people behind copies of the statue of Aphrodite, and the role of photography in archaeological knowledge production. While, “original” Greek and Roman statues are often carefully archived, preserved and exhibited as museum objects on pedestals or behind glass cases both in Cyprus and abroad, real-size copies step down from their pedestals and live an everyday life. They become domestic objects, often exposed to various weather conditions and placed alongside plants and other everyday objects. I decided to focus on one iconic statue that is found in a variety of commercial products and official documents (ex. the Cypriot passport, currency, stamps, etc.) and one that it’s often reproduced and found in gardens: the statue of Aphrodite of Soli, a marble statue from the 1st century BC and currently on display at the Cyprus Museum. The project includes mainly photographic works, silkscreens and a virtual reality (VR) experience. A part of “arte-facts” was a part of the Ar[t]chaeology Project: www.artchaeologyproject.com
Exhibition and photobook publication at Point Center for Contemporary Art, Nicosia, Cyprus
Keywords: Solo Exhibition/ Photography